Evaluasi Efektivitas Danantara dalam Mendukung Pemerataan Ekonomi dan Reformasi Perekonomian Nasional - Yudha Aditya Pradana; Wilma Silalahi (Jurnal Hukum Lex Generalis, 2024)
This study evaluates the effectiveness of Danantara, Indonesia’s Sovereign Wealth Fund, in promoting economic equity and supporting national economic reform. Established under Law No. 1 of 2025, Danantara is designed as a strategic investment institution tasked with optimizing state assets through a legal-administrative investment framework. Drawing inspiration from international models such as Temasek Holdings and Khazanah Nasional, Danantara adopts a broader mandate by consolidating state assets and enhancing inter-agency synergy. Through a normative juridical approach supported by statute, conceptual, and case-based methods, this research reveals that Danantara plays a significant role in broadening access to economic resources—particularly for MSMEs—and improving the transparency, efficiency, and sustainability of state asset management. The digitalization of assets has transformed them into active instruments of economic growth, contributing directly to job creation, regional development, and improved competitiveness in strategic sectors such as infrastructure, energy, and logistics. Despite these achievements, challenges persist in regulatory harmonization, institutional coordination, and digital infrastructure—especially in underdeveloped regions. The success of Danantara relies on strong legal oversight, adaptive policies, professional management, and continuous monitoring. The study concludes that while Danantara has demonstrated promising results in fostering inclusive growth, sustained regulatory support and cross-sector collaboration are essential to maximize its transformative potential in Indonesia’s evolving economic landscape.